Identification of natural killer markers associated with fatal outcome in COVID-19 patients - Nadine Tarantino; Elena Litvinova; Elena Litvinova; Assia Samri; Cathia Soulié; Véronique Morin; Alice Rousseau; Karim Dorgham; Christophe Parizot; Olivia Bonduelle; Alexandra Beurton; Alexandra Beurton; et al. (Frontiers in Cellular and Infection Microbiology, 2023)
IntroductionIncreasing evidence has shown that coronavirus disease 19 (COVID-19) severity is driven by a dysregulated immunological response. Previous studies have demonstrated that natural killer (NK) cell dysfunction underpins severe illness in COVID-19 patients, but have lacked an in-depth analysis of NK cell markers as a driver of death in the most critically ill patients.MethodsWe enrolled 50 non-vaccinated hospitalized patients infected with the initial virus or the alpha variant of SARS-CoV-2 with moderate or severe illness, to evaluate phenotypic and functional features of NK cells.ResultsHere, we show that, consistent with previous studies, evolution NK cells from COVID-19 patients are more activated, with the decreased activation of natural cytotoxicity receptors and impaired cytotoxicity and IFN-γ production, in association with disease regardless of the SARS-CoV-2 strain. Fatality was observed in 6 of 17 patients with severe disease; NK cells from all of these patients displayed a peculiar phenotype of an activated memory-like phenotype associated with massive TNF-α production.DiscussionThese data suggest that fatal COVID-19 infection is driven by an uncoordinated inflammatory response in part mediated by a specific subset of activated NK cells.